2020
DOI: 10.1364/oe.395273
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality display based on photo-thermo-refractive glass planar waveguide

Abstract: An augmented reality display based on a planar waveguide made in photo-thermo-refractive glass had been demonstrated. The monolithic integration of multiplexed volume Bragg gratings with the waveguide platform provided in/out-coupling and image transmission from a portable projector. Design and calculation of the grating configuration was performed. The optical replication method was simulated and implemented for manufacturing the multiplexed coupling elements. Resulted field of view was limited by the project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 16 publications
0
14
0
2
Order By: Relevance
“…The design of the phase mask itself is not the item of the research presented. It is based on a diffraction equation and starts with the periods and slant angles of the Bragg grating that needs to be achieved [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The design of the phase mask itself is not the item of the research presented. It is based on a diffraction equation and starts with the periods and slant angles of the Bragg grating that needs to be achieved [6].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have shown that for the 2 mm waveguide used, it was possible to achieve 10-20% diffraction efficiency in each of the 10 multiplexes. On the basis of described multiplex diffraction elements, it is possible to create an augmented reality waveguide guide for image transmission [6]. Figure 5b illustrates one substrate guided beam from the green laser light propagating by TIR inside the manufactured planar waveguide.…”
Section: Measurement Of Diffraction Efficiency Of Waveguide Gratingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photo-thermo-refractive (PTR) glass is a widely used multifunctional transparent material for recording volume holographic gratings [1][2][3] and fabricating a variety of integrated optical elements [4,5]. The excellent manifold properties of PTR glass are chiefly determined by its unique photosensitiveness [6] that is related to the dopants of Ag 2 O, CeO 2 , Sb 2 O 3 , and SnO 2 in trace amounts.…”
Section: Introductionmentioning
confidence: 99%
“…ФТР стекло в качестве голографической объемной среды уникально для интеграции фазовых дифракцион-ных элементов с волноводной платформой [6] и обладает высокой стойкостью к внешним воздействиям (температуре, влажности и давлению) и химической стойкостью [7]. Фазовая структура формируется непосредственно внутри среды, поэтому нет необходимости защищать световод дополнительным стеклом.…”
Section: Introductionunclassified